(untitled) (Discourse of Law and Administration, 2024)
The article points out that law teaching should not only prepare for the practice of the profession but should develop the sensitivity of the humanist needed by every lawyer. Otherwise, so ciety will be condemned to a multitude of “pharmacists” who apply the law ruthlessly. International law, as a subject of general information, can play a special role in developing social sensitivity by presenting different approaches, theoretical-legal, and philosophical perspectives. One of the pro posals is the Third World Approaches to International Law movement, which offers a view of the Third World (which brings together post-colonial, also known as the South) on the law of nations. The materialistic vision of international law and its history, visible in the views of TWAIL representati ves, proposing a critical approach to law, related to New Approaches to International Law, or Integrated Marxist Approach to International Law, can be an interesting complement to lectures on the law of nations, e.g. in the area of its history, subjectivity or human rights, going slightly beyond the main stream current based on naturalistic and positivist narrative.